A Systematic Review of the Role of Physiotherapy Interventions in Palliative Care - Tlhoiwe, Derrick D.; Tlhoiwe, Tumelo; Muya, Christine K. (Preprints, 2020)
The aim of this research is to conduct a systematic review analysing the role of the physiotherapy interventions in palliative care. PRISMA as a critical appraisal tool was utilised for the selection of the research articles. The inclusion criteria were based on the year of publication, ease of availability, language, geographical location, and study type. To ensure the credibility, databases such as Elsevier, Proquest, and EBSCO Host were used to filter the grey content. Data published in the past ten years (2009-onwards) was only included to ensure the selection of the most recent interventions used by the physiotherapists. A total of 11 articles were selected which determined that physiotherapy interventions involving breathing exercises, aerobic exercises, manual therapies, and educational awareness were critical to promoting the functional capability and empower the patients.
Keywords: Physiotherapist; Palliative Care; Physical Therapy; End-of-Life Care